Modelling, design and implementation of a small-scale, position sensorless, variable speed wind energy conversion system incorporating DTC-SVM of a PMSG drive with RLC filter - Bouwer, Pieter (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.